2021
DOI: 10.1055/a-1333-2816
|View full text |Cite
|
Sign up to set email alerts
|

Serum Selenium Levels in Glaucoma: a Pilot Study

Abstract: Background Trace elements are assumed to be involved in glaucoma pathogenesis via changes in oxidative stress. Especially serum selenium (Se) has been linked to this neurodegenerative disease. Serum Se levels differ between countries due to nutrition and ethnicity. It was the aim of the present study to investigate serum Se levels in primary open-angle glaucoma (POAG) patients and controls in Germany and to consider potential age and gender effects. Material and Methods The Se concentration of 39 ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Several studies have established a relationship between Se levels and glaucoma development [ 17 , 18 ]. However, no universally accepted Se level serves as a diagnostic or predictive marker for glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have established a relationship between Se levels and glaucoma development [ 17 , 18 ]. However, no universally accepted Se level serves as a diagnostic or predictive marker for glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors reported a correlation between Se levels in the aqueous humour and glaucoma [108,109]. Other studies demonstrated that there is no significant difference in selenium levels in glaucoma patients compared to controls [60,110]. No significant differences were observed in aqueous humour levels of selenium between patients with and without AMD [104].…”
Section: Ou L (2024) To Treat Dry Eyesmentioning
confidence: 92%
“…Selenium levels vary in human serum with age, sex, and geographical region [59]. This variation likely arises from differences in the amount of selenium (organic and inorganic) in food, water, and soil [60]. Seafood, muscle meats, cereals, grains, and dairy products are some of the foods that are high in total selenium [57].…”
Section: Selenium and Selenoproteinsmentioning
confidence: 99%